Pemetaan Sifat Fisik dan Kimia Tanah pada Tegakan Pinus merkusii di Hutan Penelitian Dramaga, Bogor - Omo Rusdiana; Nuri Nursjahbani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
The environment is a complex system where various factors affect on the plant community in the forest. This theory should be proven by study of the influence of environmental factors to the vegetation of forest stands. This study aimed to analyze the effect of environmental factors, particularly edaphic factors such as soil physical and chemical properties to the vegetation and to examine the effect of edaphic variations to the vegetation variation of Pinus merkusii stands on the plot of 163, Dramaga Forest Research, Bogor. The sample of soil were disturbed sample and undisturbed sample taken by systematic sampling method. There was a tendency that the greater the properties of soil the better the vegetation growth in terms of height and diameter of pine tree. However, that effect was not significant due to the great durability of P. merkusii against marginal soil condition. The soil properties must be supported by other factors such as shading so that the two factors are able to manage the optimal growth of pine trees and maintain the function of forest. Keywords: Pinus merkusii, physical properties, chemical properties, land unit, Dramaga